Dynamic Evaluation of Environmental Effects Associated with the Inclusion of Hydrogen-powered Vehicles in Colombia - Martinez-Escobar, Nathaly; Osorio-Gómez, Juan Carlos; Sierra-Castillo, Jose Alejandro (International Journal of Energy Economics and Policy, 2024)
Currently, the generation of CO2 emissions into the environment has increased due to the use of fossil fuels by the transportation sector and other economic sectors, motivating governments to propose mitigation actions. As a result, the search for zero-emission transportation alternatives has gained momentum, with Hydrogen technology being one of the promising solutions due to its clean and efficient energy source. In compliance with this, the Hydrogen roadmap was developed in Colombia, which seeks to encourage the use of hydrogen as a fuel and energy generator in the country. In this study, the current composition of the vehicle fleet was characterized, then a dynamic simulation model was constructed for the replacement of fossil fuel vehicles with zero-emission vehicles, considering the particularities of the country, to finally analyze the generation of CO2 in the vehicle fleet from different scenarios related to the policies proposed by the government of Colombia and stipulated in the roadmap of hydrogen. With this, it was possible to demonstrate the positive impact of taking measures for vehicle replacement in the long term. Additionally, the model could be employed in other countries, considering the particularities of the vehicle fleet and the regulations specific to the regions.